Rescue in vitro maturation may increase the pregnancy outcomes among women undergoing intracytoplasmic sperm injection - Qin, Dan-Yu; Jiang, Hua-Hua; Yao, Qing-Yun; Yao, Wen; Yuan, Xiao-Qiong; Wang, Yi; Deng, Tao-Ran; Du, Yao-Yao; Ren, Xin-Ling; Guo, Na; Li, Yu-Feng (Frontiers in Endocrinology, 2022)
Objective: To investigate whether rescue in vitro maturation (R-IVM) improves the reproductive outcomes among women undergoing intracytoplasmic sperm injection (ICSI). Design: A retrospective cohort study. Subjects: Between January 2019 and December 2020, 2602 women who underwent ICSI in the Reproductive Medicine Center of Tongji Hospital, Wuhan, China, were included in our study. There were 2112 women undergoing only ICSI and 490 women with R-IVM followed by ICSI. Main Outcome Measure(s): The intermediate reproductive outcomes and pregnancy outcomes were assessed, including the number of normally fertilized embryos, number of cleaved embryos, number of good-quality embryos, number of day-3 available embryos, number of embryos cultured past day-3, number of blastocysts, number of available blastocysts, biochemical pregnancy, miscarriage, clinical pregnancy and live birth. The perinatal outcomes were also assessed, including preterm birth and birth weight. Result(s): Compared with the women who underwent only ICSI, those who underwent ICSI with R-IVM had higher numbers of M II oocytes, normally fertilized embryos, cleaved embryos, day-3 available embryos, embryos cultured past day-3, and higher oocyte maturation rate, available embryo rate than women undergoing only ICSI. Additionally, we found that women undergoing ICSI with R-IVM had an increased chance of clinical pregnancy (adjusted OR=1.50, 95% CI: 1.17–1.93) and cumulative live birth (adjusted OR=1.35, 95% CI: 1.07–1.71). After propensity score matching (PSM), the cumulative live birth rate was 60.1% for women undergoing ICSI with R-IVM versus 54.9% for women undergoing only ICSI (OR=1.24, 95% CI: 0.94–1.63). Conclusion: ICSI with R-IVM improves the reproductive outcomes of ICSI. The comparable perinatal outcomes indicate the safety of R-IVM. This study supports a routine application of ICSI with R-IVM among patients who intend to undergo ICSI.